Strategi Cafe Luthier Coffee Palembang Untuk Mempertahankan Pelanggan - Venny Novitasari Sumantri; Herry Widagdo (FORBISWIRA FORUM BISNIS DAN KEWIRAUSAHAAN, 2023)
The aim of this research is to partially analyze the effect of service quality, product quality, brand imageand trust on customer loyalty at Luthier Coffee cafe. Another purpose is to analyze the factors of service quality,product quality, brand image and trust in customer loyalty at Luthier Coffee cafe simultaneously. The researchmethod used data collection from questionnaires with a Likert scale, with a total of 206 respondents. The type ofresearch used is descriptive quantitative. The sampling technique is nonprobability sampling with purposive samplingmethod and uses SPSS 26 software. The results of this study indicate that the partial test (t-test) of the variablesQuality of Service (X1), Product Quality (X2),Brand Image (X3) and Trust ( X4) positive and significant effect on Customer Loyalty. Simultaneous test(F-test) proves that the independent variables are Service Quality (X1), Product Quality (X2), Brand Image (X3)and Trust (X4) simultaneously affect the dependent variable namely Customer Loyalty (Y)